Economic valuation in selective solid waste collection (Sustainability in Debate, 2018)
This article aims to estimate the economic valuation of selective solid waste collection in the city of Juazeiro do Norte, Ceará, Northeast of Brazil, through the Contingent Valuation Method, presenting the average Willingness to Pay (WTP) of the respondents. Besides, it identifies the variables that influence WTP. The study involved bibliographical research and fieldwork, with 360 interviews, qualitative data analysis and statistical analysis of variables, through binary regression, using a probit model (probability unit), using STATA 11. It was found that 91.94% of the respondents recognize that selective collection contributes to the reduction of pollution, but only 37.50% would be willing to pay for the referred collection. Concerning the respondents with positive WTP, the average monthly WTP found was R$ 15.70. The higher or lower willingness to pay for the referred services was related to the variables gender, income and education. Based on the marginal effect, the variables with greater influence on WTP for selective collection in this study were gender (17.44%) and education (16.86%).